Avaliação da residência multiprofissional em saúde e o preparo para o trabalho em equipe: construção e validação de itens de uma escala atitudinal - Calvo, Marcos Estevao [UNIFESP] (2021)
Introduction - The Multiprofessional Residency in Health is a lato sensu postgraduate program. The aims of this program is to qualify health professionals with integrality and quality of care and preparing them for teamwork and collaborative practice. This type of program is having a great expansion in Brazil, so it becomes relevant to develop research to evaluation these professionals with a Interprofessional Education modality. The evaluation of experiences in Interprofessional Education is a complex process. Many evaluations studies have researched this and the most successful studies use attitudinal scales. Objectives - The aim of this study is to build and validate a set of items for an attitudinal scale to assess the preparation for Teamwork and Collaborative Practice in Multiprofessional Health Residency Programs. Method – For the construction of scales, the Pasquali's model was used. About the theory, the theoretical foundations were systematized based on research in the literature. The literature was used to support the choice of the items of the 1st version with 28 items and to subimit that to expert judges and judges of the target population. About the experimental part, we applied the 28 items of the instrument to 289 residents of the second year of Multiprofessional Residency Programs in Health (R2). With this, we reach the objective of 10 times the number of items of the instrument. About the analytical, statistical analysis of the instrument was used. Results - the Dispersion index was 0.771 and the Confiability was 0.87. It was validated 22 assertions structured in 03 dimensions: 1) The formative proposal of the Multiprofessional Residency in Health for Teamwork and Collaborative Practice (08 items); 2) The concept of Teamwork and Collaborative Practice for the resident after his residency experience (03 items) and 3) The collaborative skills developed by the resident (11 items). Final Considerations - Despite the limitations, the set of validated items can be used in future research to go deep in the study of evaluation in Multiprofessional Residency Programs in Health.